Spring tide - Börjlind, Cecilia, 1961- (Hesperus Nova, 2014)
A gripping, cinematic crime thriller from the scriptwriters known as the king and queen of Scandinavian crime, expertly crafted and full of twists and turns The spring tides are the highest of the year in Nordkoster; the beach will be covered in particularly deep water tonight. Three men on the beach are digging a hole, covertly watched by a young boy. His intrigue turns to horror as he makes out the fourth figure of the woman for whom the hole is intended. Buried up to her neck in the sand, the high tide is rapidly approaching. Still screaming in terror, the victim takes her last breath as water fills her nose and mouth--in her stomach, she feels her baby kick. And her waters break. The abhorrent crime remains unsolved 24 years later; but gruesome violence is still prevalent. A gang has been killing homeless people in parks, filming their attacks, and broadcasting them on the internet. The police have their work cut out trying to keep abreast of the crime wave. Olivia Rönning hopes to follow in her father's footsteps and join their ranks in the next few months as she completes her training; she has only one last hurdle to overcome over the summer break, a challenge from her professor to pick a cold case and solve it. Should be simple, she thinks. Little does she know the world she is getting involved in, the danger she faces, and the ugly truths she risks uncovering.